Primary school autonomy in the context of the expanding academies programme. (January 2018) - Boyask, Ruth
The transnational trend towards school autonomy has been enacted in England through the academies programme. The programme is poised to enter its third phase of expansion in light of government commitment to the conversion of all state-funded schools to academies. This article considers the moral implications of the expansion of the programme that aims to include all primary schools. It draws upon a study of schools in four local authorities to examine the extent to which autonomy and therefore academy conversion is desirable. In their relationships with local authorities, primary schools that have resisted conversion and primary schools that have already converted show ambivalence to the notion of autonomy which has been promoted by the government as motivation to convert. Indeed most of the primary schools in this study that have already converted are critical of the local authorities that are driven by business values. Given that expansion of the academies programme is likely to lead to more rather than less fragmentation in the education system, worsen student outcomes overall and see market values extended, it is concluded that the vision of autonomy for primary schools offered via the academies programme is both misleading and undesirable.